PERAN HUKUM HUMANITER INTERNASIONAL DALAM MEMFASILITASI REKONSILIASI PASCA-KONFLIK: ANALISIS KOMPARATIF KASUS-KASUS KONTEMPORER - Rado Parulian Purba (JOURNAL OF LAW AND NATION, 2025)
Post-conflict reconciliation is a critical component in addressing the legacy of violence and preventing the recurrence of armed conflict. This research analyzes how the principles and mechanisms of International Humanitarian Law (IHL) contribute to the post-conflict reconciliation process by comparing four contemporary cases: Colombia, Rwanda, Bosnia-Herzegovina, and Timor-Leste. Using a qualitative approach with comparative case study methods, this research evaluates the implementation of IHL in the reconciliation process through analysis of official documents, international organization reports, and in-depth interviews with 25 humanitarian law experts and reconciliation actors. The results show that effective implementation of IHL through transitional justice mechanisms positively correlates with successful long-term reconciliation. Three main elements of IHL that contribute significantly to reconciliation are: accountability for serious violations, recognition of victims' suffering, and rehabilitation of affected communities. However, the implementation of IHL in reconciliation faces challenges in the form of limited institutional capacity, tensions between justice and political stability, and lack of sustained international support. This research concludes that IHL needs to be holistically integrated into national reconciliation frameworks with consideration of the cultural and social context of post-conflict societies